Analisis Dampak Gaya Kepemimpinan, Motivasi Kerja,Gaya Komunikasi Dan Disiplin Kerja TerhadapKinerja Guru Di Karanganyar(Studi Perbandingan Di Sekolah Umum Dan Islam Di Karanganyar) - , Nurdiyanta, Muhammad Sholahuddin,SE.,M.Si (2016)
This study aims to determine the impact of leadership style, employee motivation, communication style and discipline of work on teacher performance in Karanganyar. This research is quantitative. The population in this study is were all teachers in public schools and Islam in Karanganyar which amounted to 140 people and the sample used in this study was 100 respondents. Analysis of the data used in this study were using multiple linear regression analysis Based on the results of the research show leadership style has no impact on teacher performance as indicated by the significant value of 0.279> 0.05. The motivation of teachers has an impact on teacher performance demonstrated with significant value 0.027 <0.05. The style of communication has an impact on teacher performance demonstrated with significant value 0.000 <0.05. Labor discipline have no impact on teacher performance as indicated by the significant value of 0914> 0.05. Together variable variable leadership style, employee motivation, communication style, and discipline to be significantly influential work on teacher performance as evidenced by the significant value 0.000 <0.05 Keywords: Leadership Style. Work motivation. Communication styles. Communication styles. Work Discipline.